2000
DOI: 10.1080/03601230009373255
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dimethoate on the immune system of female mice

Abstract: The functional status of the immune system of female mice exposed to a single oral dose of dimethoate (16 mg/kg) was evaluated by assessing cell mediated and humoral immune responses, in addition to the effect of dimethoate on spleen and body weights after different time intervals. The data showed that dimethoate caused a time-depended decrease in spleen weights in the absence of a change in body weights. The immunologic effect of dimethoate to female mice produced a dose-dependent decrease in the number of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The lack of consistent dose response trends with all the exposure metrics might support chance as the explanation for the observed associations, or it might imply some mechanism different from a direct intervention in the carcinogenic process. For instance, dimethoate was shown to have the lowest cytotoxic and genotoxic potential in cultured cells, compared to other three organophosphates and the organochlorine endosulfan;80 however, its administration in experimental female mice caused a decrease in total immunoglobulins and IgM and in the number of plaque forming cells;81 the same effects were observed over three generations following repeated administration of low doses dimethoate in outbred Wistar rats 82. Functional activity of Th1 lymphocytes, immune reactions associated with these cells, and interferon- γ  production were impaired after subacute malathion intoxication in albino rats,83 while thymic atrophy and reduction in splenic germinal centres followed methylparathion administration in rabbits 84.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of consistent dose response trends with all the exposure metrics might support chance as the explanation for the observed associations, or it might imply some mechanism different from a direct intervention in the carcinogenic process. For instance, dimethoate was shown to have the lowest cytotoxic and genotoxic potential in cultured cells, compared to other three organophosphates and the organochlorine endosulfan;80 however, its administration in experimental female mice caused a decrease in total immunoglobulins and IgM and in the number of plaque forming cells;81 the same effects were observed over three generations following repeated administration of low doses dimethoate in outbred Wistar rats 82. Functional activity of Th1 lymphocytes, immune reactions associated with these cells, and interferon- γ  production were impaired after subacute malathion intoxication in albino rats,83 while thymic atrophy and reduction in splenic germinal centres followed methylparathion administration in rabbits 84.…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with some previous reports, Blakley et al (1999) reported that humoral immunity (anti-sheep red blood cell), a T-lymphocyte macrophage dependent response, was reduced in rats when CPF administered by oral gavage twice weekly for 28 days at a dose of 5.0 mg/kg. Also, Aly and El-Gendy, (2000) found that a single oral dose of dimethoate (16 mg/kg) significantly decreased serum total immunoglobulins (Ig) and IgM, while IgG was non-significantly . deceased.…”
Section: Discussionmentioning
confidence: 99%
“…11 In fact, the toxicity of organophosphorus insecticides results in negative effects on many organs and systems such as the liver, kidney, nervous system, immune system, and reproductive system. 12,13 The liver is one of the organs affected by malathion toxicity. It showed degenerative changes in the form of congestion of the central vein and focal areas of leucocytic infiltration in the hepatic architecture.…”
Section: Discussionmentioning
confidence: 99%